Amphiphilic Fluorescent Well-Defined Living Polymer from Indole-3-Carboxaldehyde and 4-Bromo-1, 8-Naphthalic Anhydride: Synthesis and Characterization. (10th March 2014) - Srivastava, Ambika; Singh, Pooja; Srivastava, Arti; Kumar, Rajesh
Abstract : We reported a well-defined amphiphilic fluorescent polymer bearing indole repeating units with naphthalimide pendants obtained by ATRP followed by chemical modification. The obtained polymer poly (N-allyl indole-2-(4-hydroxybutyl)-1, 8-naphthalimide) (PAIHN) was characterized by 1 H NMR, FTIR, and GPC. The polymer showed a specific fluorescence emission maximum at 538 nm excited at 435 nm in aqueous solution. The amphiphilic nature of the polymer was investigated in aqueous solution using two spectroscopic methods, namely, absorption and emission spectroscopy. The Critical Miceller Concentration values obtained by UV-visible and fluorescence are in good agreement with each other. The micelles were characterized by TEM at concentration of 0.014 mg/mL. The polymer PAIHN prepared after tweaking exhibits green fluorescence at 538 nm due to the significant effect of naphthalimide moieties, whereas before tweaking the polymer poly (1-allyl indole-3-carbaldehyde) (PAIC) exhibits blue fluorescence at 425 nm due to indole repeating units of the polymer.